Colorectal endoscopic submucosal dissection in special locations - Kaosombatwattana, Uayporn (World J Gastrointest Endosc, 2019)
Colorectal endoscopic submucosal dissection (ESD) is considered one of the most challenging endoscopic procedures for novice endoscopists. When compared with the stomach, the colon and rectum have a narrower tubular lumen, greater angulation at the flexures, and a thinner muscle layer. These factors make endoscopic control and maneuverability difficult. ESD of the colorectum was considered more difficult than gastric and esophageal ESD. However, with learning from the experts, practicing, and selecting an appropriate technique, most of colorectal ESD could be performed successfully. Nevertheless, some colorectal locations are extremely specialized either from unique anatomy or given unstable scope position. Accordingly, the objective of this review was to provide endoscopists with an overview of the techniques and outcomes associated with ESD at these special colorectal locations. ESD at the discussed special locations of the ileo-colo-rectum was found to be feasible, and outcomes were comparable to those of ESD performed in non-special locations of the ileo-colo-rectum. Practice for skill improvement and awareness of the unique characteristics of each special location is the key to performing successful ESD.